Development of a Printed Sensor and Wireless Measurement System for Urination Monitoring - Lan Zhang; En Takashi; Jian Lu; Sohei Matsumoto (Sensors)
The development of reliable and efficient sensors is essential for advances in health monitoring technologies. This study focused on the fabrication and evaluation of a multichannel printed sensor electrode designed for long-term stability and effective data acquisition. Using rapid printing technology, we created a urine sensor array with extended electrodes for the measurement of urine volume and frequency. The ultrathin design of the sensor electrode, with an average thickness of only 30 microns, ensures both user comfort and measurement accuracy. The sensor electrode dimensions were meticulously designed, measured, and optimized through successful trial manufacturing of the sensor electrode and sensor array. Comprehensive evaluation of the fabricated sensor demonstrated excellent performance, including a high response speed of ≤1 s and long-term stability exceeding 5 weeks. In addition, wireless transmission capabilities and user interfaces were developed for field experiments. Finally, animal experiments were performed to evaluate the field performance of the fabricated sensor. Accordingly, we are confident that the sensor developed herein will contribute to enhancing healthcare in an aging society.